Post-Marxism and Class Struggle - Arditi, Benjamin (Bollettino Filosofico, 2025)
This is an exploratory article about class struggle, an unfashionable term since the dissolution of the Soviet Union and the global ascendancy of market society. I look at class struggle not as a unitary experience but as clusters of struggles between those who contest inequality and demand dignity and those largely unconcerned by their persistence. I examine four approaches to class: as a structural position; as infrapolitics operating outside the formal public sphere; as the becoming-class of the underdogs; and as unilateral warfare waged by elites without necessarily leading to direct resistance. I then assess a conceptualization of class beyond the mode of production. Keywords: Class, Class Struggle, Dignity, Inequality, Post-Marxism